SARS-CoV-2-Specific CD8+ T-Cells in Blood but Not in the Lungs of Vaccinated K18-hACE2 Mice after Infection - Flavia Ferrantelli; Francesco Manfredi; Chiara Chiozzini; Patrizia Leone; Katherina Pugliese; Massimo Spada; Antonio Di Virgilio; Andrea Giovannelli; Mauro Valeri; Andrea Cara; Zuleika Michelini; Mauro Andreotti; et al. (Vaccines, 2023)
Severe acute respiratory syndrome coronavirus (SARS-CoV)-2 enters the host by infecting nasal ciliated cells. Then, the virus can spread towards the oropharyngeal cavity and the pulmonary tissues. The antiviral adaptive immunity is promptly induced in response to the virus’s detection, with virus-specific T-lymphocytes appearing before antiviral antibodies. Both the breadth and potency of antiviral CD8+ T-cell immunity have a key role in containing viral spread and disease severity. Current anti-SARS-CoV-2 vaccines do not impede the virus’s replication in the upper respiratory tract, and there is consensus on the fact that the best potency of the antiviral immune response in both blood and the upper respiratory tract can be reached upon infection in vaccinees (i.e., breakthrough infection). However, whether the antiviral CD8+ T-cells developing in response to the breakthrough infection in the upper respiratory tract diffuse to the lungs is also still largely unknown. To fill the gap, we checked the CD8+ T-cell immunity elicited after infection of K18-hACE2 transgenic mice both at 3 weeks and 3 months after anti-spike vaccination. Virus-specific CD8+ T-cell immunity was monitored in both blood and the lungs before and after infection. By investigating the de novo generation of the CD8+ T-cells specific for SARS-CoV-2 viral proteins, we found that both membrane (M) and/or nucleocapsid (N)-specific CD8+ T-cells were induced at comparable levels in the blood of both unvaccinated and vaccinated mice. Conversely, N-specific CD8+ T-cells were readily found in the lungs of the control mice but were either rare or absent in those of vaccinated mice. These results support the idea that the hybrid cell immunity developing after asymptomatic/mild breakthrough infection strengthens the antiviral cell immunity in the lungs only marginally, implying that the direct exposition of viral antigens is required for the induction of an efficient antiviral cell immunity in the lungs.